ANALISIS YURIDIS PENETAPAN WALI BADAN YG NGAWAS OLEH BHP DALAM RANGKA MELINDUNGI WEWENANG KEPERDATAAN ANAK (CONTOH PUTUSAN NOMOR: 0014/PDT.P/2015/PA.MN). - Rhenal Cokronegoro; Mulati . (Jurnal Hukum Adigama, 2018)
Children are gifts from God Almighty that we must guard and that we must protect, because children are also human beings who have rights and dignity as human beings. One of the rights of the child is the right to enjoy the wealth of his parents, including inheritance. Many children whose parents experience problems, such as divorce or one or both parents die. In order for a child to do a legal act, he needs a guardian in carrying out legal actions. Guardians here have a function to represent all children's needs in carrying out legal actions. In guardianship, there is a guardian’s overseer whose function is to oversee the guardian in terms of managing the assets of the child, in this case is the Heritage Hall. The Heritage Hall has two functions, namely as guardians of supervisors in charge of guarding guardians, as well as temporary guardians. The problem here is that the Heritage Hall is not cared for by the community, so not all guardianship verdicts use the trustees in it. whereas the Law clearly stipulates that the Heritage Hall must be the trustee in every trusteeship order ordered in the State of Indonesia.